Preparation method of large-size CuInS2 quantum dots

Large-sized CuInS2 quantum dots were synthesized by a secondary growth method, which solved the problems of small size and insufficient luminescence of existing CuInS2 quantum dots, and improved the luminescence performance in the near-infrared -II region. The preparation process is also simple.

CN121674059APending Publication Date: 2026-03-17HEBEI UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511899878.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-12-16
Publication Date
2026-03-17

AI Technical Summary

Technical Problem

The small size of existing CuInS2 quantum dots limits their luminescence performance in the near-infrared II region, and traditional preparation methods are costly and energy-intensive, making it difficult to meet the needs of emerging bioimaging fields.

Method used

Large-sized CuInS2 quantum dots were synthesized using a secondary growth method. Using dodecyl mercaptan as the sulfur source, cuprous iodide as the copper source, and indium acetate as the indium source, the secondary growth of CuInS2 cores was achieved by controlling the heating program and stirring rate, resulting in a size of 9.16 nm and a redshift of the emission peak to 1120 nm.

Benefits of technology

The prepared CuInS2 quantum dots have large size characteristics, stable luminescence, and can meet the luminescence requirements of the near-infrared -II region. Moreover, the preparation process is simple, requires no additional modification, and exhibits a significant redshift phenomenon in luminescence.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The invention provides a preparation method of a large-size CuInS2 quantum dot. The invention belongs to the field of semiconductor luminescent nano materials, and provides a novel synthesis method for obtaining a CuInS2 quantum dot material with the size of 9.16 nm, the photoluminescence peak position of 1120 nm and the electroluminescence peak position of 1045 nm. The n-dodecanethiol is used as a sulfur source, the cuprous iodide is used as a copper source, the indium acetate is used as an indium source, the operation is convenient, the large-size near-infrared stable luminous CuInS2 material can be obtained through one-time heating, and the material has the advantages of wide spectrum and low toxicity. The large-size CuInS2 semiconductor quantum dot material prepared by the preparation method disclosed by the invention can obtain near-infrared luminescence under the excitation of ultraviolet wavelength. The synthesis process is simple, and stable quantum dots can be obtained without further modification treatment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of semiconductor nano-quantum dot luminescent materials, specifically a method for preparing large-size CuInS2 quantum dots. Background Technology

[0002] Quantum dots are nanoscale semiconductor particles with unique optoelectronic properties, typically ranging in size from a few nanometers to tens of nanometers. When these quantum dots reach the nanometer scale (smaller than the exciton Bohr radius), a "quantum confinement" effect occurs in the region around them, where the electronic energy levels near the Fermi level split from a continuous state into discrete energy levels. This effect gives quantum dots unique optical properties, such as absorption and emission. The size of a quantum dot directly affects its band structure; therefore, by precisely adjusting the size of quantum dots, it is possible to achieve wide-range modulation of emission wavelengths, from the ultraviolet to the visible and even infrared regions.

[0003] Compared to visible fluorescence, near-infrared fluorescence offers significant advantages in hypersensitive in vivo imaging and multispectral bioimaging applications due to its superior tissue penetration and lower background interference. Near-infrared (NIR)-II wavelengths (1000–1700 nm) exhibit higher spatial resolution, deeper penetration into the biological matrix, lower optical absorption and scattering, and minimal tissue autofluorescence compared to the visible light region (400–700 nm) and near-infrared I (700–900 nm). Currently, non-invasive imaging techniques utilizing NIR-II fluorescence and photoacoustic (PA) imaging demonstrate the immense appeal of NIR-II optical imaging. Therefore, NIR-II bioimaging is receiving increasing exploration due to its significant potential in preclinical research and clinical applications. CuInS2 quantum dots (CIS QDs) possess unique photoelectric properties, are non-toxic, and have good biocompatibility, enabling their application in fluorescent probes, real-time bioimaging, and medical diagnostics. However, the relatively small size of CuInS2 quantum dots limits their luminescence in the near-infrared II region. How to solve the problems of high preparation cost, high energy consumption and inability to meet the emission requirements of more than 1000 nm in emerging fields of traditional near-infrared luminescent QDs materials is an urgent research task in the field of semiconductor nano-quantum dot luminescent materials. Summary of the Invention

[0004] The purpose of this invention is to provide a method for preparing large-size CuInS2 quantum dots. This invention synthesizes large-size CuInS2 quantum dot materials through secondary seed growth. Compared with CuInS2 grown by primary nucleation, the size of CuInS2 grown by secondary seed growth can reach 9.16 nm, and the photoluminescence peak of this CuInS2 quantum dot is at 1120 nm, which is more than 150 nm redshift compared with similar materials.

[0005] This invention is implemented as follows: The large-size CuInS2 quantum dot material mentioned in this invention is synthesized using dodecanethiol (DDT) as the sulfur source, cuprous iodide as the copper source, and indium acetate as the indium source. Specifically, the preparation method involves a two-stage growth process. Based on a primary nucleation, pyrolyzed raw materials are added to the nucleus for adsorption and growth, resulting in a CuInS2 nucleus size that is twice that of the primary nucleation nucleus. This achieves a size adjustment effect, causing the CuInS2 quantum dot emission peak to redshift to 1120 nm.

[0006] The preparation method of this large-size CuInS2 quantum dot material is as follows: a. Weigh cuprous iodide and indium acetate in a molar ratio of 1:1, add the weighed cuprous iodide and indium acetate to flask A, then add n-dodecyl mercaptan dropwise, and then add a magnetic stir bar for stirring. b. Place flask A on a heating controller to carry out the heating reaction. Set its heating program in the following order: ① At room temperature, heat to 100 ℃ in 10 min and hold for 10 min; ② Heat to 230 ℃ in 10 min and maintain nucleation and growth at this temperature. c. Weigh cuprous iodide and indium acetate in a molar ratio of 1:1, add the weighed cuprous iodide and indium acetate to flask B, then add dodecyl mercaptan dropwise, and then add a magnetic stir bar for stirring. d. Place flask B on a heating controller to carry out the heating reaction. Set its heating program as follows: ① At room temperature, heat to 100 ℃ in 10 min and hold for 10 min; ② Heat to 160 ℃ within 5 min; By controlling the initial heating time of flask B, make the end time of step ② heating of flask B coincide with the end time of step ② nucleation and growth of flask A. e. Quickly inject the solution from flask B into flask A to perform secondary growth of CuInS2 nuclei; f. After the secondary growth is completed and cooled, anhydrous ethanol is added and centrifuged. The resulting precipitate is dissolved in toluene to obtain large-sized CuInS2 quantum dots.

[0007] Preferably, in step b, nucleation and growth are carried out at 230 °C for 20-30 min.

[0008] More preferably, in step b, nucleation and growth are carried out at 230 °C for 20 min.

[0009] Preferably, in step e, the heating temperature of flask A is controlled at 220°C, and the time for secondary growth of CuInS2 nuclei is 20~30 min.

[0010] More preferably, in step e, the heating temperature of flask A is controlled at 220°C, and the time for secondary growth of CuInS2 nuclei is 30 min.

[0011] Preferably, the magnetic stirring rate in steps a and c is 800 r / min.

[0012] Preferably, flask A in step a and flask B in step c are purged with N2 for 10 min before use.

[0013] The CuInS2 quantum dots prepared by this invention are liquid QDs with stable luminescence. They can be freeze-dried with the addition of tert-butanol to obtain powder materials, and can also be used to fabricate stable light-emitting devices on ITO substrates.

[0014] The present invention has the following advantages: Firstly, the CuInS2 quantum dots obtained are large-sized quantum dots and exist in both solid and liquid states; secondly, the preparation process of the CuInS2 quantum dots is simple and does not require additional steps for modification; thirdly, the CuInS2 quantum dots have large-size characteristics, and according to the quantum confinement effect, the increase in size will reduce the energy level restriction of the quantum dots, resulting in a significant redshift phenomenon in emission. Attached Figure Description

[0015] Figure 1 These are the PL spectra of the samples prepared in Comparative Examples 1 to 4 of this invention.

[0016] Figure 2 This is a TEM image of the sample prepared in Comparative Example 1 of this invention.

[0017] Figure 3 This is a TEM image of the sample prepared in Example 1 of the present invention.

[0018] Figure 4 This invention measures Figure 2 and Figure 3 The TEM image shown is a statistical distribution diagram of the precise size of 120 grains; where (a) is the size statistical diagram of the sample in Comparative Example 1, and (b) is the size statistical diagram of the sample in Example 1.

[0019] Figure 5 These are photographs of the sample prepared in Example 1 of this invention after being diluted to different concentrations and taken under natural light.

[0020] Figure 6These are infrared camera images taken under blue light excitation of samples prepared in Example 1 of this invention after being diluted to different concentrations.

[0021] Figure 7 This is a comparison of the XRD patterns of the samples prepared in Example 1 and Comparative Example 1 of the present invention with the CuInS2 (JCPDS 27-0159) standard card.

[0022] Figure 8 This is the PL and absorption spectrum of the sample prepared in Example 1 of the present invention.

[0023] Figure 9 This is an electroluminescence (EL) image of the sample prepared in Example 1 of the present invention.

[0024] Figure 10 These are PL diagrams of the samples prepared in Example 1 and Comparative Example 1 of the present invention. Detailed Implementation

[0025] To make the objectives, technical solutions, and advantages of this invention clearer, further explanation is provided below in conjunction with the accompanying drawings.

[0026] Comparative Example 1: CuInS2 (CIS) material was obtained by single-stage nucleation.

[0027] Weigh out cuprous iodide (190.5 mg) and indium acetate (291.9 mg) in a 1:1 molar ratio. Add the weighed raw materials to a 50 mL three-necked flask. Add 10 mL of dodecanethiol (DDT) dropwise to the flask and then place it under a magnetic stirrer at a speed of 800 r / min. Place the flask under a temperature controller for heating the reaction. Set the temperature program and raise the temperature to 100 °C in 10 min at standard room temperature (25 °C), and hold for 10 min to make the solution clear and transparent. Then, heat to 230 °C within 10 min and maintain this temperature for nucleation and growth for 30 min. After the experiment, cool the flask, add anhydrous ethanol, centrifuge, and dissolve the precipitate in toluene to obtain CuInS2 material.

[0028] Comparative Example 2 Compared with Comparative Example 1, the nucleation and growth time was changed to 60 min, while all other aspects were the same as Comparative Example 1.

[0029] Comparative Example 3 Compared with Comparative Example 1, the nucleation and growth time was changed to 90 min, while all other aspects were the same as Comparative Example 1.

[0030] Comparative Example 4 Compared with Comparative Example 1, the nucleation and growth time was changed to 120 min, while all other aspects were the same as those in Comparative Example 1.

[0031] The samples prepared in Comparative Examples 1-4 were measured on a HORIBA Fluorolog-3 fluorescence spectrometer, and the PL spectra of the samples were obtained as follows: Figure 1 As shown. By Figure 1 It can be seen that the luminescence intensity of the sample gradually decreases with the increase of nucleation time. Moreover, its luminescence peak position is slightly red-shifted, but its luminescence intensity gradually decreases significantly.

[0032] The sample prepared in Comparative Example 1 was diluted in toluene and then dropped onto a 300-mesh copper TEM grid. TEM (transmission electron microscopy) measurements were performed on a JEOL 2100F operating at 200 kV. The results are as follows: Figure 2 As shown in the figure, the sample size is approximately 5 nm.

[0033] Example 1: Large-size CuInS2 (CIS) quantum dot materials were obtained through secondary growth.

[0034] Weigh out cuprous iodide (190.5 mg) and indium acetate (291.9 mg) in a 1:1 molar ratio. Add the weighed raw materials to a 50 mL three-necked flask A. Add 10 mL of dodecanethiol (DDT) dropwise to three-necked flask A and then place it in a magnetic stirrer at a stirring speed of 800 r / min. Prepare three-necked flask B in the same manner. Place three-necked flask A and three-necked flask B on a heating thermostat for the reaction. The heating program for three-necked flask A is as follows: ① At standard room temperature (25 °C), raise the temperature to 100 °C in 10 min and hold for 10 min until the solution becomes clear and transparent; ② Heat to 230 °C within 10 min and maintain this temperature for nucleation and growth for 20 min. The heating program for three-necked flask B was as follows: ① At standard room temperature (25 °C), the temperature was increased to 100 °C in 10 minutes and held for 10 minutes to make the solution clear and transparent; ② The temperature was increased to 160 °C within 5 minutes. By controlling the initial heating time of the two three-necked flasks, the end time of step ② of the two three-necked flasks was ensured to coincide, that is, when three-necked flask B was heated to 160 °C within 5 minutes, three-necked flask A had exactly been nucleating and growing at 230 °C for 20 minutes. Then, the solution in three-necked flask B was rapidly injected into three-necked flask A using a glass syringe, and the heating program of three-necked flask A was set to 220 °C and held for 30 minutes. After the experiment, the solution was cooled, anhydrous ethanol was added, and the mixture was centrifuged. The resulting precipitate was dissolved in toluene to obtain large-size CuInS2 quantum dot material (liquid).

[0035] The sample prepared in Example 1 was subjected to TEM (transmission electron microscopy) measurements. Specifically, the sample was further diluted in toluene, then dropped onto a 300-mesh copper TEM grid, and TEM measurements were performed on a JEOL 2100F operating at 200 kV. The results are as follows. Figure 3 As shown. From Figure 2 and Figure 3 Size statistical analysis was performed on 120 CuInS2 quantum dots selected in each sample. The results are shown in [Figure number missing]. Figure 4 .Depend on Figure 4 It can be seen that the CuInS2 quantum dots obtained in Example 1 have a size of about 9 nm, while the CuInS2 quantum dots obtained in Comparative Example 1 have a size of about 4.8 nm. Therefore, the size of the secondary-grown CuInS2 nuclei in this embodiment of the invention is about twice the size of the primary CuInS2 nucleation.

[0036] The liquid CuInS2 quantum dots prepared in Example 1 were diluted to concentrations of 10, 5, 1, and 0.5 mg / mL, and placed in four different glass bottles. Photographs of the four bottles were taken under natural light as follows: Figure 5 As shown in the figure. Visually, the sample at a concentration of 10 mg / mL was the darkest, appearing dark brown. Infrared imaging was performed on these four samples at different concentrations under blue laser (365 nm) excitation, and the results are as follows. Figure 6 As shown in the figure, the sample emits light when excited by blue light.

[0037] The samples prepared in Example 1 and Comparative Example 1 were analyzed by X-ray diffraction, and the XRD spectra were obtained as follows: Figure 7 As shown in the figure, it can be clearly seen that the peak positions of the samples prepared in Example 1 and Comparative Example 1 correspond to the CuInS2 standard card, and the diffraction peak intensity of the sample prepared in Example 1 is higher than that of Comparative Example 1.

[0038] Figure 8 The PL and absorption spectra of the sample prepared in Example 1 are shown. The PL spectrum of the sample was measured on a HORIBA Fluorolog-3 fluorescence spectrometer, and the absorption spectrum was measured on a Lambda 950 UV-Vis spectrometer. Figure 9 The image shows the electroluminescence (EL) pattern of the sample prepared in Example 1. Figure 10 This is a comparison graph of the PL values ​​of the samples prepared in Example 1 and Comparative Example 1. Figures 8-10 It can be seen that the PL emission peak of the sample obtained in Example 1 is at 1120 nm, and the EL emission peak is at 1045 nm, while the PL emission peak of the sample obtained in Comparative Example 1 is at 970 nm. Therefore, the PL emission peak of the CuInS2 quantum dots obtained by secondary nucleation growth in this invention is red-shifted by 150 nm compared to the sample obtained by primary nucleation growth.

Claims

1. A method for preparing large size CuInS2 quantum dots, characterized in that, It comprises the following steps: a. Take cuprous iodide and indium acetate according to the molar ratio of 1:1, add the taken cuprous iodide and indium acetate into flask A, then add dodecanethiol dropwise, and then put into a magnetic stirrer for stirring; b. Put flask A on a heating temperature controller for heating reaction, and set the heating program as follows: ① at room temperature, increase the temperature to 100 ℃ for 10 min and keep for 10 min; ② heat to 230 ℃ within 10 min, and keep at this temperature for nucleation and growth; c. Take cuprous iodide and indium acetate according to the molar ratio of 1:1, add the taken cuprous iodide and indium acetate into flask B, then add dodecanethiol dropwise, and then put into a magnetic stirrer for stirring; d. Put flask B on a heating temperature controller for heating reaction, and set the heating program as follows: ① at room temperature, increase the temperature to 100 ℃ for 10 min and keep for 10 min; ② heat to 160 ℃ within 5 min; By controlling the starting heating time of flask B, the time point at which the heating of flask B in step ② ends coincides with the time point at which the nucleation and growth of flask A in step ② ends; e. Extract the solution in flask B and quickly inject into flask A for secondary growth of CuInS2 nucleus; f. After the secondary growth, cool, add anhydrous ethanol for centrifugation, dissolve the obtained precipitate with toluene to obtain large-size CuInS2 quantum dots.

2. The method of claim 1, wherein the CuInS2 quantum dots have a size of 10 nm or more. In step b, the nucleation and growth is performed at 230 ℃ for 20-30 min.

3. The method of claim 2, wherein the CuInS2 quantum dots have a size of 5 nm or more. In step b, the nucleation and growth is performed at 230 ℃ for 20 min.

4. The method of claim 1, wherein the CuInS2 quantum dots have a size of 10 nm or more. In step e, the heating temperature of flask A is controlled to be 220 ℃, and the secondary growth time of CuInS2 nucleus is 20-30 min.

5. The method of claim 4, wherein the CuInS2 quantum dots have a size of 5 nm or more. In step e, the secondary growth time of CuInS2 nucleus is 30 min.

6. The method of claim 1, wherein the CuInS2 quantum dots have a size of 10 nm or more. In steps a and c, the stirring rate of the magnetic stirrer is 800 r / min.

7. The method of claim 1, wherein the CuInS2 quantum dots have a size of 10 nm or more. In step a, flask A and in step c, flask B are blown with N2 for 10 min before use.

8. Large-size CuInS2 quantum dots prepared by the method according to any one of claims 1-7.